Compositional Phase Change of Early Transition Metal Diselenide (VSe2 and TiSe2) Ultrathin Films by Postgrowth Annealing. Issue 15 (8th June 2020) - Bonilla, Manuel; Kolekar, Sadhu; Li, Jiangfeng; Xin, Yan; Coelho, Paula Mariel; Lasek, Kinga; Zberecki, Krzysztof; Lizzit, Daniel; Tosi, Ezequiel; Lacovig, Paolo; Lizzit, Silvano; Batzill, Matthias
Abstract: The transition metal selenides M1+ y Se2 (M = V, Ti) have intriguing quantum properties, which make them target materials for controlling properties by thinning them to the ultrathin limit. An appropriate approach for the synthesis of such ultrathin films is by molecular beam epitaxy. Here, it is shown that such synthesized V‐ and Ti‐Se2 films can undergo a compositional change by vacuum annealing. Combined scanning tunneling and photoemission spectroscopy is used to determine compositional and structural changes of ultrathin films as a function of annealing temperature. Loss of selenium from the film is accompanied by a morphology change of monolayer height islands to predominantly bilayer height. In addition, crystal periodicity and atomic structure changes are observed. These changes are consistent with a transition from a layered transition metal dichalcogenide (TMDC) to ordered intercalation compounds with V or Ti intercalated in between two layers of their respective TMDCs. These observations may clear up misconception of the nature of previously reported high‐temperature grown transition metal selenides. More significantly, the demonstrated control of the formation of intercalation compounds is a key step toward modifying properties in van der Waals systems and toward expanding material systems for van der Waals heterostructures. Abstract : Monolayer films of the early transition metal diselenides (VSe2 and TiSe2 ) undergo compositional and structural transitions by vacuum annealing to a self‐intercalation compound. Annealing leads to a selenium loss and the liberated transition metals intercalate in between transition metal dichalcogenide layers to form an ordered intercalation compound.